2010
DOI: 10.1007/s00268-010-0740-9
|View full text |Cite
|
Sign up to set email alerts
|

Resident Workload, Pager Communications, and Quality of Care

Abstract: With the recent regulations limiting resident work hours, it has become more important to understand how residents spend their time. The volume and content of the pages they receive provide a valuable source of information that give insight into their workload and help identify inefficiencies in hospital communication. We hypothesized that above a certain workload threshold, paging data would suggest breakdowns in communication and implications for quality of care. All pages sent to six general surgery interns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…15610–12 Patel et al studied pager messages sent to surgical interns at the University of Michigan Health System. 1 Paging data was reported over 18 months and were coded by two investigators who individually assigned sender type, message type, message modifier, and page quality. A total of 9,843 messages were received by the six interns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15610–12 Patel et al studied pager messages sent to surgical interns at the University of Michigan Health System. 1 Paging data was reported over 18 months and were coded by two investigators who individually assigned sender type, message type, message modifier, and page quality. A total of 9,843 messages were received by the six interns.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past 20 years, clinicians have faced an increasing communication burden, due in part to the proliferation of devices such as pagers, smart phones, and tablets. 13 Until the last several years, one-way numeric paging has been the main route of communication among clinicians and other multidisciplinary teams. The introduction of alphanumeric paging has allowed one-way communication to take place without the recipient having to respond via telephone call to each numeric page.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional method of using pagers as a means of communication is far from ideal; 65% interrupt patient care,1 a quarter are unimportant or unnecessary and only one-third actually result in a change to care 1 2. Junior doctors receive on average 60 bleeps per on-call shift, with peaks during nursing handover, increased volumes with reduced nursing workload, and only 16 min between bleeps at peak times 3. To address these problems junior doctors often resort to personal mobile phones, which are carried by 98%, and are used by 67% for work-related matters at an average cost of £14/month for hospital-related calls 4.…”
Section: Introductionmentioning
confidence: 99%
“…Research about the impact of trainee work-hour restrictions has exposed the communications burden experienced by resident physicians, much of which may be non-essential 6 7. A study of pager communications revealed that general surgery residents received an average of 57 (±3) pager communications or ‘pages’ during an ‘on-call’ shift, and that the proportion of urgent messages increased as resident workload increased 6.…”
mentioning
confidence: 99%
“…A study of pager communications revealed that general surgery residents received an average of 57 (±3) pager communications or ‘pages’ during an ‘on-call’ shift, and that the proportion of urgent messages increased as resident workload increased 6. Nearly half the surgeries involving resident physicians are interrupted at least twice, and the overwhelming majority of the interruptions were later determined to be non-urgent 7.…”
mentioning
confidence: 99%